Presence and characterization of Escherichia coli virulence genes isolated from diseased pigs in the central region of Argentina - Bessone, Fernando Aníbal; Bessone, Gabriela; Marini, Sebastián José; Conde, María Belén; Alustiza, Fabrisio Eduardo; Zielinski, Gustavo Carlos (2018)
Background: The main pathogen of neonatal and post weaning diarrhea and edema disease (ED) is Escherichia coli and pathotypes involved are enterotoxigenic, enteropathogenic, and shiga toxigenic (ETEC, EPEC, and STEC, respectively). Those diseases cause economic loss in pig production. Aim: The aim of this work was to evaluate the presence of strains expressing virulence markers genes and the antibiotic susceptibility profiles of E. coli from clinical cases of post weaning diarrhea and ED in farms in the central area of Argentina. Materials and Methods: Intensive pig farms from the central region of Argentina were sampled. Intestinal mucosa swabs from pigs with diarrhea were taken, seeded on MacConkey agar plates, biochemically typified and tested by polymerase chain reaction (PCR). Antibiograms were made by disk-diffusion method. Results: A total of 54 strains from clinical cases studied showed PCR findings: 88.88% (48/54) expressed at least one gene coding for a virulence factor. Colonization factors found were: 39.58% of strains had F18, 33.33% were F4 and 31.25% adhesin involved in diffuse adherence-I; 29.17%, 25%, and 2.1% expressed LT, STb, and STa, respectively. 25% were STx and 16.67% were eae positive. Only 2.1% were STx2. The most active antibiotics against most strains were gentamicin and ceftiofur, but resistance profiles against many antibiotics were found. Conclusion: High circulation of pathogens strains of E. coli among pigs with diarrhea with an extended antibiotic resistance profile.